1288PSafety and efficacy of anti-PD-1 inhibitor ABBV-181 in lung and head and neck carcinoma. (1st October 2019) - Italiano, A; Cassier, P; Roda, D; Lin, C-C; Peltola, K; Gazzah, A; Shiah, H-S; Calvo, E; Tosi, D; Gao, B; warburton, L; Tanner, M; et al.
Abstract: Background: ABBV-181 is a humanized anti-PD1 monoclonal antibody; dose finding and early safety, PK and pharmacodynamic data have been reported (ESMO18). This report summarizes data from the head and neck squamous cell carcinoma (HNSCC) and non-small cell lung cancer (NSCLC) expansion cohorts in the Ph1 FIH study (NCT03000257). Methods: Patients (pts) with previously treated, advanced HNSCC and NSCLC received ABBV-181 IV, 250 mg Q2W or 500 mg Q4W to progression. Response was assessed by RECIST v1.1 and iRECIST. Results: As of April 2019, 81 pts were dosed. Conclusions: Safety, PK and PD data support dosing ABBV-181 at 250 mg Q2W or 500 mg Q4W with expected biological and pharmacodynamic activity for an anti-PD-1 agent. Efficacy data demonstrate clinical activity per RECISTv.1.1 and iRECIST supporting continued development of ABBV-181. Clinical trial identification: NCT03000257. Editorial acknowledgement: Fatemeh Atashi (AbbVie employee). Legal entity responsible for the study: AbbVie Inc. Funding: AbbVie Inc. Disclosure: A. Italiano: Advisory / Consultancy: Roche, Daiichi Sankyo, ImmuneDesign, Epizyme, Bayer, Lilly; Honoraria (self): Bayer, Daiichi Sankyo, Lilly, Epizyme, Novartis, Roche; Research grant / Funding (self): Roche, Bayer, AstraZeneca/MedImmune, PharmaMar, MSD Oncology, Merck Serono. P. Cassier: Honoraria (self): Novartis, Roche/Genentech, Blueprint Medicines, Amgen; Research grant / Funding (institution): Novartis, Roche/Genentech, Lilly, Blueprint Medicines, Bayer, AstraZeneca, Celgene, Plexxikon, AbbVie, Bristol-Myers Squibb, Merck Serono, Merck, Sharp and Dohme. C. Lin: Advisory / Consultancy: Novartis, Boehringer Ingelheim, Blueprint Medicines; Travel / Accommodation / Expenses: Lilly, Daiichi Sankyo, BeiGene, Novartis; Honoraria (self): Novartis, Roche, Daiichi Sankyo. K. Peltola: Advisory / Consultancy: Orion Pharma, BMS, MSD, Pfizer, Ipsen and Roche; Shareholder / Stockholder / Stock options: Faron Pharmaceuticals; Speaker Bureau / Expert testimony: BMS, Pfizer, MSD; Speaker Bureau / Expert testimony: Ipsen; Travel / Accommodation / Expenses: Roche and BMS. A. Gazzah: Travel / Accommodation / Expenses: Boehringer, Novartis, Pfizer, Roche. E. Calvo: Advisory / Consultancy: Novartis, Nanobiotix, Janssen-Cilag, PsiOxus, Seattle Genetics, EUSA Pharma, AbbVie, Celgene, AstraZeneca, Guidepoint Global, Roche/Genentech, GLG, Pfizer, Servier, Amcure; Speaker Bureau / Expert testimony: Novartis; Research grant / Funding (self): AstraZeneca, BeiGene, Novartis, START, Oncoart Associated, ; Leadership role: President and Founder of Foundation Intheos. D. Tosi: Advisory / Consultancy: Biomarin ; Research grant / Funding (self): Novartis, Astellas, Janssen; Travel / Accommodation / Expenses: Janssen, Pfizer, and Astellas Pharma, Nutricia and Amicus. B. Gao: Advisory / Consultancy: MSD. L. warburton: Travel / Accommodation / Expenses: MSD, Merck. M. Tanner: Advisory / Consultancy: Roche, Novartis and Pfizer; Speaker Bureau / Expert testimony: Roche, Novartis, Pfizer and Amgen. S. Englert: Full / Part-time employment: AbbVie Inc.; Shareholder / Stockholder / Stock options: AbbVie Inc. S. Lambert: Full / Part-time employment: AbbVie Inc.; Shareholder / Stockholder / Stock options: AbbVie Inc. A. Parikh: Shareholder / Stockholder / Stock options: AbbVie Inc.; Full / Part-time employment: AbbVie Inc. D. Afar: Shareholder / Stockholder / Stock options: AbbVie Inc.; Full / Part-time employment: AbbVie Inc. G. Vosganian: Shareholder / Stockholder / Stock options: AbbVie Inc.; Full / Part-time employment: AbbVie Inc. V. Moreno: Advisory / Consultancy: Merck; Travel / Accommodation / Expenses: Regeneron/Sanofi; Research grant / Funding (self): Medscape/Bayer. All other authors have declared no conflicts of interest.